PRODUÇÃO CIENTÍFICA DE ENFERMAGEM EM NEFROLOGIA, NO BRASIL, NO PERÍODO DE 1989 ATÉ 1999 - Lourdes Maria Silva Andraus; Raquel Linhares Melo; Indira Matos Pinheiro Carvalho (Universidade Federal de Goias, 2001)
Research of quantity character exploratory retrospective with the aim of raising the publications about nursing nephrology at Revista Brasileira de Enfermagem, informations about researchs and Brazilian Society of Nursing in Nephrology between January 1989 and December 1999. The dates were collected on the thirst using form. 1997 was the year with the biggest number of publications and São Paulo stood out in quantity of publications and the most found methodology was masterly dissertation. We conclude that nursing nephrology is a good area for researches that will revert in improvement of assistance.